Reprint - Martens, Karel; Koninklijke Academie van Beeldende Kunsten (Netherlands) (Arnhem : Roma Publications, 2015)
This book is published on the occasion of an exhibition of work by Dutch designer Karel Martens at the Royal Academy of Arts in The Hague. Besides offering a closer look at his free work, it also covers his approach to the teaching of graphic design. Comprising a selection of both past work and more recent applied work, it also includes new essays by David Bennewith, who examines Martens' approach to teaching through its history and accounts from students, and Robin Kinross, who offers a meditation on the artist's free work, which demonstrates a consistent line of inquiry through his 54 years in graphic design. Martens was the recipient of the Gerrit Noordzij Prize in 2012. Exhibition: Royal Academy of Art, The Hague, The Netherlands (03.2015).
Catalog of an exhibition held at Royal Academy of Art, The Hague, Netherlands, March, 2015.
Imported from: prospector.coalliance.org:210/INNOPAC (Do not remove)
boek
Keywords: Martens, Karel; Graphic arts -- Exhibitions; Commercial art -- Exhibitions; Graphic design (Typography)